Computational modeling of the out-of-plane behavior of unreinforced irregular masonry. (15th November 2020) - Mercuri, Micaela; Pathirage, Madura; Gregori, Amedeo; Cusatis, Gianluca
Highlights: Analysis of the out-of-plane behavior of unreinforced irregular masonry structures. LDPM reproduces the damage evolution and fracture propagation in irregular masonry. Realistic failure predictions of a variety of complex mechanisms and configurations. LDPM is an alternative to limit analysis in assessing local collapse mechanisms. Walls openings and boundary conditions govern local and global collapse mechanisms. Abstract: The vulnerability of stone masonry structures to seismic loading constitutes one of the main application areas of research in the field of structural engineering. This paper focuses on the analysis of the out-of-plane response of unreinforced masonry structures. Although successful in many applications, traditional continuum-based analysis, as well as simplified analytical models, fail to a large extent in correctly capturing complex failure mechanisms occurring for this type of structures. To overcome this issue, this study adopts a discrete model, the so-called Lattice Discrete Particle Model (LDPM), to describe the structural behavior of a variety of stone masonry structures up to their collapse. LDPM simulates the behavior of masonry at the stone level. The interaction between stones that are bounded by weak layers of mortar is governed by specific constitutive equations describing tensile fracturing with strain-softening, cohesive and frictional shearing, and compressive response with strain-hardening. This manuscript aims to validate the proposed model with experimental data available in the literature. Furthermore, overturning walls with and without openings are simulated, the associated local collapse mechanisms are analyzed and compared with the classical kinematic analysis. Finally, more complex mechanisms are numerically investigated to reproduce the behavior of systems of panels included within the continuity of a facade. The results show that LDPM is able to capture the damage evolution and the fracture propagation that lead to the overall collapse and it can be used confidently as an alternative method to perform the limit analysis of local collapse mechanisms. The proposed numerical approach provides engineers with a powerful modeling tool for the analysis of the behavior of stone masonry structures with a variety of geometrical configurations and under very general loading conditions.